Bridging the gap between water-saving technologies and adoption in vegetable farming: insights from Florida, USA - Athelly, Akshara; Guzmán, Sandra M.; Yu, Ziwen; Watson, Jonathan Adam (Frontiers in Agronomy, 2025)
Globally, agricultural water management faces significant challenges due to uneven water availability, crop diversity, and climate variability. Despite increasing access to smart irrigation technologies, adoption among vegetable farmers remains low. This study examines the willingness of Florida vegetable growers to adopt water-saving irrigation technologies, focusing on socio-economic factors, perceived barriers, and opportunities for enhanced outreach. A structured, pre-tested survey was conducted with commercial vegetable growers across Florida’s major vegetable-producing regions, collecting data on irrigation practices, familiarity with technology, satisfaction, and demographic characteristics. Results showed that satisfaction with current irrigation practices and willingness to adopt new technologies were significantly influenced by farm size, education, income, and crop diversity. Farmers managing multiple crops, small-scale growers expressed a strong interest in adoption, particularly when cost-share or technical assistance programs were available. Common barriers included high initial costs, lack of technical training, and skepticism about the reliability of water-saving technologies. This study highlights the need for targeted outreach strategies that consider demographic variability, farm size, and cropping systems. Based on the results, the policy measures that simplify access to incentive information, decision-support tools, and inclusive hands-on training programs can enhance technology adoption. While focused on Florida, the findings reflect broader patterns in adoption behavior across global small- to medium-scale farming systems. These insights are valuable for policymakers, extension agents, and researchers aiming to accelerate the adoption of precision irrigation for climate-resilient agriculture.